Isokinetic Peak of Torque and Fatigue Index in Simulated Wheelchair Propulsion in Elite Wheelchair Rugby Players - Machado, Felipe; Correia, Renan Felipe; Ribeiro, Alex Natalino; Neto, Samuel Ribeiro dos Santos; Vieira, Ivaldo Brandão; Gorla, José Irineu (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: In sports such as wheelchair rugby, the correct assessment and quantification of an athletes’ peak of torque and fatigue index in sport-specific actions are essential in monitoring an athletes’ training performance. The increase in the number of people practicing Paralympic sports has been growing exponentially, contributing to an increase of competition level and of athletes’ performance. Objective: Thus, physical training for Paralympic sport must aim to maximize athletes’ fitness potential by investigating and evaluating what variables are most important in determining ideal sporting performance. Methods: Six high-level wheelchair rugby athletes had their wheelchair propulsion peak of torque and fatigue index evaluated by isokinetic dynamometry in three different angular velocity and repetition schemes. Results: The athletes presented no significant statistical difference in peak of torque and fatigue index for both arms at different number of repetitions and angular velocity. Conclusions: This shows that independent of dexterity parameters or duration of stimuli, these high-level athletes display this motor skill in constant levels of performance. These results will allow coaches to set up normative parameters to test and evaluate their players’ performances.